Faktor-Faktor Psikologis yang Mempengaruhi Postpartum Blues - Susanti Prasetya Ningrum (Psympathic : Jurnal Ilmiah Psikologi, 2017)
Pregnancy and childbirth are the natural and normal processes experienced by every woman. In the process of pregnancy and childbirth every woman undergoes both physical and psychological changes so that women need to be prepared before entering this stage. Those who are not ready will be more likely to experience postpartum blues. This study aimed to determine the psychological factors that affect postpartum blues. The method was quantitative correlational with purposive sampling technique. Participating mothers were 6 months postpartum (n=41). The research instruments were Edinburgh Postnatal Depression Scale (EPDS), coping stress scale, social support scale, and adjustment scale. The data was analyzed by simple linear regression. The result of this study showed that from the three independent variables giving predictions the biggest influence on the emergence of postpartum blues were adjustment variable (56,3%), then coping stress (46,1%), and social support (30,2%).